Analisis kemampuan pemecahan masalah matematis siswa SMK pada materi SPLTV ditinjau berdasarkan gender - Idan Wildan Akhyar; Eka Senjayawati (IKIP Siliwangi, 2023)
This study aims to analyze students' mathematical problem solving abilities, especially in the material of the Three Variable Linear Equation System (SPLTV) using qualitative methods. The subjects of this study were class X students of TI Garuda Nusantara Cimahi Vocational School with a sample of 36 students with 18 male students and 18 female students. As for the data collection technique in this study, namely by testing the description test questions which amounted to 5 description questions tested on students based on indicators of mathematical problem solving ability; (1) Understanding the problem, (2) Planning to solve the problem, (3) Resolving the problem, and (4) Re-examining the process and results. Based on the results and discussion of the research, it can be said that the highest score indicator obtained by students is found in the first indicator, namely understanding the problem with a percentage of 61.11% and the one with the lowest score is the indicator of re-examining results with a percentage of 8.34% of the total percentage. . Meanwhile, when viewed from gender, female students have better problem-solving skills than males.